Application of metagenomics sequencing to diagnose paralytic rabies with stroke-like onset: a case report - Baoquan Lin; Dan Zhong; Lu Qin; Qianqian Liu; Liya Wu; Bo Wang; Kuliang Wang; Xianfu Lu; Shan Deng; Liya Pan (Frontiers in Medicine)
BackgroundRabies is an acute zoonotic infectious disease caused by infection with a virus of the genus Lyssavirus. We report a case of paralytic rabies with a stroke-like onset, which was diagnosed using metagenomics next-generation sequencing (mNGS).Case presentationA 58-year-old man was admitted to the hospital with “numbness and weakness in the right upper extremity for 2 days, aggravated for 1 day.” Twenty-five days before his admission, the patient was bitten on the back of right hand by an unvaccinated domestic dog, resulting in a penetrating injury, classified as grade III according to the rabies exposure classification method. Following admission, the patient exhibited rapidly progressive stroke symptoms, and on the second day, he suffered a sudden respiratory arrest accompanied by a weakened heartbeat and a decreased heart rate. He was treated with emergency tracheal intubation, cardiopulmonary resuscitation, and dehydration to lower cranial pressure.ResultsThe patient’s condition deteriorated rapidly after admission. A lumbar puncture was conducted on the morning of the second day of admission, and cerebrospinal fluid (CSF) was sent to Weiyuan Genetic Laboratories (Guangzhou, China) for rabies virus identification. The patient died on the third day of admission. Pathogen capture macro-genomics was performed on CSF using an Illumina NextSeq second-generation sequencer, and nine rabies virus sequences, which shared more than 99% nucleotide homology with the genome sequence of the rabies virus Rabies lyssavirus (NCBI accession no. MN175989.1), were detected. The Q30 ratio of this test was 98.3%.ConclusionCompared to polymerase chain reaction (PCR) and direct fluorescent antibody (DFA) test, mNGS shortens the diagnostic window and improves sensitivity to low-virus or seronegative manifestations by simultaneously capturing and sequencing the entire pathogen genome. The mNGS technology can effectively aid in the diagnosis of paralytic rabies.